Does fiscal consolidation promote economic growth and employment? Evidence from the PIIGGS countries - Philip Arestis; Ayşe Kaya; Hus̈eyin Şen (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2018)
Using annual data over the period 1980–2014, this paper attempts to provide an answer to the question of whether fiscal consolidation promotes growth and employment in the context of the PIIGGS countries (Portugal, Ireland, Italy, Greece, Great Britain, and Spain) by using the Bootstrap Granger causality analysis proposed by Kónya (2006), which allows testing for causality on each individual country separately, and by accounting for dependence across countries. Our findings indicate that in no country considered does fiscal consolidation promote growth. However, fiscal consolidation negatively affects employment in Portugal and Italy, whereas it positively influences employment in Great Britain. Based on our findings, we may suggest that the effects of fiscal consolidation on employment produce mixed results, varying from country to country.
Keywords: C23; E62; H50; H62; 330; fiscal consolidation; growth; employment; PIIGGS countries; panel Granger causality analysis